GP.1 Changes in ischemic stroke presentations and associated workflow during the first wave of the COVID-19 pandemic: A population study. (November 2021) - Ganesh, A; Stang, JM; McAlister, FA; Shlakhter, O; Holodinsky, JK; Mann, B; Hill, MD; Smith, EE
Abstract : Background: Pandemics may promote hospital avoidance among patients with emergencies, and added precautions may exacerbate treatment delays. Methods: We used linked administrative data and data from the Quality Improvement and Clinical Research Alberta Stroke Program – a registry capturing stroke-related data on the entire Albertan population(4.3 million) – to identify all patients hospitalized with stroke in the pre-pandemic(01/01/2016-27/02/2020) and COVID-19 pandemic(28/02/2020-30/08/2020) periods. We examined changes in stroke presentation rates and use of thrombolysis and endovascular therapy(EVT), adjusted for age, sex, comorbidities, and pre-admission care needs; and in workflow, stroke severity(National Institutes of Health Stroke Scale/NIHSS), and in-hospital outcomes. Results: We analyzed 19, 531 patients with ischemic stroke pre-pandemic versus 2, 255 during the pandemic. Hospitalizations/presentations dropped(weekly adjusted-incidence-rate-ratio[aIRR]:0.48, 95%CI:0.46-0.50), as did population-level incidence of thrombolysis(aIRR:0.49, 0.44-0.56) or EVT(aIRR:0.59, 0.49-0.69). However, proportions of presenting patients receiving thrombolysis/EVT did not decline (thrombolysis:11.7% pre-pandemic vs 13.1% during-pandemic, aOR:1.02, 0.75-1.38). For out-of-hospital strokes, onset-to-door times were prolonged(adjusted-coefficient:37.0-minutes, 95%CI:16.5-57.5), and EVT recipients experienced greater door-to-reperfusion delays(adjusted-coefficient:18.7-minutes, 1.45-36.0). NIHSS scores and in-hospital mortality did not differ. Conclusions: The first COVID-19 wave was associated with a halving of presentations and acute therapy utilization for ischemic stroke at a population level, and greater pre-/in-hospital treatment delays. Our data can inform public health messaging and stroke care in future pandemic waves.